(untitled) (The International Journal for Scientific Research, 2023)
An experiment was carried out to find out how laying hen performance, egg quality, and serum metabolites were affected by adding soybean bioactive peptide (SBP) and vitamin E to their diet. Ninety Lohmann Extra hens that were 45 weeks old were divided into five groups at random. Each group consisted of three replicates, each with six birds. The dietary treatments included 250 mg/kg of vitamin E added to the baseline diet, 2.5, 5, and 7.5 g/kg of diet for the SBP groups, and the basal diet as the control. The findings demonstrated that egg production rate and egg weight significantly increased with SBP supplementation (P≤0.05). While there were no appreciable changes between the vitamin E-treated groups and the control group, there was a noticeable difference in feed efficiency between the SBP groups and the control group. Peptides-supplemented groups showed a definite advantage in terms of egg quality attributes, as evidenced by the weights of egg components, yolk index, and albumin index. The SBP supplement also resulted in an increase in glutathione peroxides (GSH-PX) and superoxide dismutase (SOD). Additionally, compared to the positive control treatment (adding vitamin E), there was a substantial (P≥0.05) drop in the cholesterol levels in the yolk among the groups supplemented with peptides. The group that got an excessive amount of soybean peptide (5 g/kg) had the highest serum total antioxidant activity. The findings concluded that adding SBP to the diets can enhance egg quality and production while also influencing the hens’ serum’s total antioxidant activity during the laying phase.